AKTIVITAS ANTIBAKTERI DAN KOMPONEN KIMIA EKSTRAK HEKSAN, ETIL ASETAT DAN ETANOL BATANG BROTOWALI (Tinospora crispa Linn) ASAL MANOKWARI - Bimo Budi Santoso; Argina Argina; Alfhons D. Sirampun (Jurnal Natural, 2020)
Antibacterial activity test and chemical component analysis of hexane, ethyl acetate and ethanol extract of Brotowali stem from Manokwari Regency against B. subtillis and E. coli have been carried out. The extraction of the T. crispa stems was carried out by the maceration method in stages based on the polarity of the solvent. Chemical component analysis was performed using GC-MS and phytochemical tests. Based on the identification of chemical compounds by phytochemical screening, it shows the presence of flavonoids in the hexane extract, while in the ethyl acetate and ethanol extracts there are alkaloids, flavonoids, saponins, and tannins. The results of the chemical component analysis of hexane, ethyl acetate and ethanol extracts with GC-MS showed that the hexane extract contained 55 chemical components with 11 main components, ethyl acetate extract consisted of 39 components with 8 main components and ethanol extract there were 57 components with 8 main components. The results of the antibacterial activity test using the well method showed that the hexane and ethyl acetate extracts showed better antibacterial activity than the ethanol extract against the two types of tested bacteria, namely E. coli and B. subtillis. The antibacterial activity of hexane and ethyl acetate extracts against E. coli was 11.00 and 14.00 mm, respectively and against B. subtillis were 7.00 and 7.50 mm, respectively.